The response of soil organic nitrogen to the application of green manure mixed with phosphate fertilizer at manure microsite on acidic soil - Huang, Jiapu; Hong, Jiwang; Arango, Jacobo; Huang, Dongfen; Huan, Hengfu (Multidisciplinary Digital Publishing Institute, 2025)
The application of green manure (GM), particularly leguminous varieties, demonstrates significant benefits for crop cultivation in acidic soils by enhancing the soil organic nitrogen (No) pool. To maximize these agronomic advantages, it is crucial to implement scientifically grounded application strategies. To this end, an incubation experiment was conducted to investigate the content, movement distance, and accumulation of acidic soil organic N (No) at different distances from the GM application microsite. Stylosanthes GM (10 or 40 ton/ha) was applied with or without phosphate fertilizer (monocalcium phosphate, MCP) at 44 kg/ha P, placed on the surface of soil cylinders. The GM/fertilizer and soil were incubated for 14 and 28 d. The results indicated the total organic nitrogen (TNo) content—including both non-acid-hydrolyzable N (NAHNo) and acid-hydrolyzable N (AHNo) fractions—significantly (p < 0.05) increased at the GM microsite after GM application. The influence of GM generally weakened as the distance from the site increased, and the spatial impact range exhibited significant modulation by three key parameters: incubation period, GM rates, and MCP addition. Subsequent analysis revealed a positive correlation between GM rate/incubation period and the movement distance of No fractions at GM microsite, demonstrating rate-dependent temporal dynamics. They were also increased by the addition of MCP after a longer incubation period but inhibited after a shorter period. This information will improve the efficiency of GM use, with or without MCP addition, and decrease the environmental load due to N pollution caused by GM.